Method for preparing synthesis gas through rare earth modified all-solid-state electrolytic tank
By depositing rare earth oxide nanocatalysts on the SFM cathode surface of the all-solid electrolytic cell, the problem of insufficient cathode stability and catalytic activity is solved, and efficient co-electrolysis preparation of synthesis gas is achieved, cost reduction, and energy circulation is used for rare earth resources.
Patent Information
- Application Number
- CN202411788795.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
AI Technical Summary
The existing all-solid-state electrolytic cells have poor cathode stability when operating at high temperatures, and have problems with carbon deposition and Ni coarseness, and their catalytic activity is not sufficient to meet the needs of efficient co-electrolysis to prepare synthesis gas.
The synthesis gas method is prepared by rare earth modified all-solid electrolytic cell, and different rare earth oxide nanocatalysts are deposited on the surface of the SFM cathode through chemical impregnation to improve the adsorption and activation ability of CO2 and H2O.
The catalytic activity and cathode stability of all solid electrolytic cells are improved, efficient co-electrolysis preparation of synthesis gas is achieved, cost reduction, and the rare earth resources in the region are used to achieve efficient circulation and rational utilization of energy.
Smart Images

Figure CN119615191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing synthesis gas by using a rare earth modified all-solid-state electrolytic cell. Background Art
[0002] With the rapid development of the global economy and the steady rise of industrialization, energy consumption and carbon dioxide emissions have further accelerated. At present, about 70% of carbon dioxide emissions come from the extensive use of fossil fuels, which has a great impact on global warming and climate change. High-temperature solid oxide electrolysis cells (HT-SOECs) can use renewable energy sources such as wind and solar energy to electrolyze CO2 and H2O into syngas (a mixture of H2 and CO) fuel gas. Its higher operating temperature improves the reaction kinetics and enhances the efficiency of electrolysis. And as an all-solid-state electrolysis cell, SOEC has high practical value. Thanks to its high conversion efficiency and low power consumption for electrolysis, it has the prospect of large-scale deployment. The co-electrolysis technology using SOEC has developed rapidly in recent years.
[0003] Traditional SOECs use ion conductor yttrium-stabilized zirconia as electrolyte, metal Ni-composite YSZ as cathode, and strontium-doped lanthanum manganese (LSM) as anode material. Although the Ni-YSZ cathode has good catalytic activity for H2O and CO2 electrolysis, carbon deposition and Ni coarsening will occur during long-term operation of the electrolytic cell, which is not conducive to electrolysis. Therefore, seeking cathode materials with high catalytic activity, high conductivity, and resistance to carbon deposition has become one of the focuses of co-electrolysis research. Sr2Fe 1.5 Mo 0.5 O 6-δ As a double perovskite cathode material, it has been widely studied as a SOEC cathode. Based on its excellent structural stability and resistance to carbon deposition, it is a suitable alternative to traditional Ni-YSZ. However, its adsorption capacity for H2O and CO2 is poor, resulting in its catalytic activity not meeting the requirements. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing synthesis gas using a rare earth modified all-solid-state electrolytic cell, wherein the all-solid-state electrolytic cell used has good catalytic activity and can realize efficient co-electrolysis to prepare synthesis gas.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell comprises the following steps:
[0007] S1. The SSZ powder is poured into a mold and pressed into a cylindrical SSZ green billet, and the SSZ green billet is sintered at high temperature for 5-10h to obtain a SSZ electrolyte layer;
[0008] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly to obtain a cathode slurry;
[0009] S3. The LSCF-SDC electrode powder and the organic glue are mixed evenly to obtain an anode slurry;
[0010] S4. The SDC powder and pinene alcohol are mixed evenly to obtain an isolation layer slurry, the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers, and the electrolyte is sintered at high temperature for 3-6h to obtain an SDC|SSZ|SDC electrolyte;
[0011] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form an SFM cathode layer, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form an LSCF-SDC anode layer, and sintering at high temperature for 1-5h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0012] S6. The rare earth salt solution and the surfactant are mixed to obtain a rare earth solution, and the rare earth solution is impregnated into the outer surface of the SFM cathode layer obtained in step S5 with a microsyringe under a vacuum environment, and then dried and sintered for 1-2h;
[0013] S7. Repeat step S6, and finally sinter for 0.5-5h to obtain a rare earth-modified all-solid-state electrolytic cell;
[0014] S8. The all-solid-state electrolytic cell obtained in step S7 is sealed on an alumina tube, CO2 and H2O are introduced into the SFM cathode layer after heating, and then current is applied to achieve the preparation of synthesis gas.
[0015] Furthermore, in step S1 of the present invention, the SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 The powder is pressed at a pressure of 10 MPa, the bottom diameter of the SSZ green billet is 20 mm, the high-temperature sintering temperature is 1400-1600° C., and the thickness of the electrolyte layer is 150-220 μm.
[0016] Furthermore, in step S2 of the present invention, the weight ratio of SFM electrode powder, pore-forming agent and organic glue is 1:1:0.5, and the SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is one or more of activated carbon, graphite, corn starch or PMMA, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24. The main function of the pore-forming agent is to adjust the porosity and microstructure of the cathode layer.
[0017] Furthermore, in step S3 of the present invention, the weight ratio of LSCF-SDC electrode powder to organic glue is (0.5-3):1, and the LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24.
[0018] Furthermore, in step S4 of the present invention, the weight ratio of SDC powder to terpineol is 1:1, and the SDC powder is Sm 0.2 Ce 0.8 O2 powder; the high temperature sintering temperature is 1150-1250°C, and the thickness of the isolation layer is 2-5μm.
[0019] Furthermore, in step S5 of the present invention, the temperature of high temperature sintering is 1100-1400° C., and the thickness of the SFM cathode layer and the LSCF-SDC anode layer are both 15-35 μm.
[0020] Further, in step S6 of the present invention, the weight ratio of the rare earth salt solution and the surfactant is 1:(0.02-0.05), the concentration of the rare earth salt solution is 0.1-0.5 mol / L, the rare earth salt is one or more of the nitrates or chlorides of Ce, Pr, Sm, Gd, Nd, and La elements, and the surfactant is one or more of citric acid, glycine, urea, ethylene glycol, ethanol, or triethanolamine; the drying temperature is 80°C, the drying time is 1-2h, and the sintering temperature is 400-800°C. The role of the surfactant is to enhance the wettability of the solution and reduce the phase formation temperature, and the role of sintering is to decompose the rare earth salt into rare earth oxides and deposit them on the SFM cathode layer.
[0021] Furthermore, in step S7 of the present invention, the weight ratio of the rare earth salt to the SFM electrode powder is (0.02-0.1):1, and the sintering temperature is 400-800°C.
[0022] Furthermore, in step S8 of the present invention, the temperature of the heating is 650-850°C, the volume ratio of the introduced CO2 and H2O is (0.1-9):1, and the current density is 0.1-2A·cm -2 .
[0023] Another technical problem to be solved by the present invention is to provide a rare earth modified all-solid-state electrolytic cell prepared by the above preparation method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The present invention adopts a chemical impregnation method to prepare different rare earth oxide nanocatalysts, modifies the surface of the SFM electrode, and utilizes the oxygen vacancies of the rare earth oxide nanocatalyst to increase the chemical adsorption active sites, thereby enhancing the adsorption and activation of CO2 and H2O, thereby efficiently realizing the co-electrolysis to prepare synthesis gas.
[0026] 2) The materials used in the method of the present invention can all be domestically produced, with low cost and easy implementation, which is far lower than the traditional noble metal nanoparticle modification method. At the same time, it can make full use of the rare earth resources in the local area, realize the efficient circulation and rational utilization of energy, solve the cathode stability problem of the solid oxide electrolytic cell when operating at high temperature, and avoid the shortcomings of the traditional cathode during operation, such as carbon deposition and the need to add a protective atmosphere to prevent oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:
[0028] Figure 1 It is a schematic diagram of the process flow of the present invention and a schematic diagram of the microstructure of rare earth oxides;
[0029] Figure 2 Schematic diagram of XRD test results of Example 1, Examples 4-7 and Comparative Examples of the present invention;
[0030] Figure 3 A single cell structure diagram and a schematic diagram of the battery microstructure of Example 1 of the present invention;
[0031] Figure 4 It is a comparison chart of IV performance of 800°C co-electrolysis of Example 1, Examples 4-7 and Comparative Example of the present invention. DETAILED DESCRIPTION
[0032] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0033] Example 1
[0034] The synthesis gas is prepared as follows:
[0035] S1. Pour SSZ powder into a mold and press it under 10MPa pressure to form a cylindrical SSZ blank with a bottom diameter of 20mm. Sinter the SSZ blank at 1500℃ for 8h to obtain a 200μm thick SSZ electrolyte layer. The SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89Powder;
[0036] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly in a weight ratio of 1:1:0.5 to obtain a cathode slurry. The SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is activated carbon, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0037] S3. The LSCF-SDC electrode powder and organic glue are mixed evenly in a weight ratio of 2:1 to obtain an anode slurry. The LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0038] S4. SDC powder and pinene alcohol in a weight ratio of 1:1 are mixed evenly to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers with a thickness of 3 μm, and sintered at 1200°C for 5h to obtain an electrolyte with a structure of SDC|SSZ|SDC, where the SDC powder is Sm 0.2 Ce 0.8 O2 powder;
[0039] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form a SFM cathode layer with a thickness of 25 μm, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form a LSCF-SDC anode layer with a thickness of 25 μm, and sintering at 1300° C. for 5 h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0040] S6. A rare earth salt solution with a concentration of 0.5 mol / L and a surfactant in a weight ratio of 1:0.03 are uniformly mixed to obtain a rare earth solution, and the rare earth solution is impregnated with a microsyringe on the outer surface of the SFM cathode layer obtained in step S5 under a vacuum environment, and then dried at 80°C for 1.5h and sintered at 600°C for 1h, wherein the rare earth salt is Ce(NO3)3·6H2O and the surfactant is citric acid;
[0041] S7. Repeat step S6 to make the weight ratio of Ce(NO3)3·6H2O to SFM electrode powder 0.06:1, and finally sinter at 800°C for 3h to obtain a rare earth modified all-solid-state electrolytic cell;
[0042] S8. The all-solid-state electrolytic cell obtained in step S7 was sealed on an alumina tube, the temperature was raised to 850°C, CO2 and H2O with a volume ratio of 1:1 were introduced into the SFM cathode layer, and 0.2A·cm -2 The current was measured to obtain the IV curve of the battery, and the composition of the synthesis gas was tested by gas chromatography (GC).
[0043] Example 2
[0044] The synthesis gas is prepared as follows:
[0045] S1. Pour SSZ powder into a mold and press it under 10MPa pressure to form a cylindrical SSZ blank with a bottom diameter of 20mm. Sinter the SSZ blank at 1500℃ for 8h to obtain a 200μm thick SSZ electrolyte layer. The SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 Powder;
[0046] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly in a weight ratio of 1:1:0.5 to obtain a cathode slurry. The SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is activated carbon, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0047] S3. The LSCF-SDC electrode powder and organic glue are mixed evenly in a weight ratio of 2:1 to obtain an anode slurry. The LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0048] S4. SDC powder and pinene alcohol in a weight ratio of 1:1 are mixed evenly to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers with a thickness of 3 μm, and sintered at 1200°C for 5h to obtain an electrolyte with a structure of SDC|SSZ|SDC, where the SDC powder is Sm 0.2 Ce 0.8 O2 powder;
[0049] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form a SFM cathode layer with a thickness of 25 μm, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form a LSCF-SDC anode layer with a thickness of 25 μm, and sintering at 1300° C. for 5 h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0050] S6. A rare earth salt solution with a concentration of 0.5 mol / L and a surfactant in a weight ratio of 1:0.03 are uniformly mixed to obtain a rare earth solution, and the rare earth solution is impregnated with a microsyringe on the outer surface of the SFM cathode layer obtained in step S5 under a vacuum environment, and then dried at 80°C for 1.5h and sintered at 600°C for 1h, wherein the rare earth salt is Ce(NO3)3·6H2O and the surfactant is glycine;
[0051] S7. Repeat step S6 to make the weight ratio of Ce(NO3)3·6H2O to SFM electrode powder be 0.02:1, and finally sinter at 800°C for 3h to obtain a rare earth modified all-solid-state electrolytic cell;
[0052] S8. The all-solid-state electrolytic cell obtained in step S7 was sealed on an alumina tube, the temperature was raised to 650°C, CO2 and H2O with a volume ratio of 0.1:1 were introduced into the SFM cathode layer, and 0.1A·cm -2 The composition of the synthesis gas was tested by gas chromatograph (GC).
[0053] Example 3
[0054] The synthesis gas is prepared as follows:
[0055] S1. Pour SSZ powder into a mold and press it under 10MPa pressure to form a cylindrical SSZ blank with a bottom diameter of 20mm. Sinter the SSZ blank at 1500℃ for 8h to obtain a 200μm thick SSZ electrolyte layer. The SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 Powder;
[0056] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly in a weight ratio of 1:1:0.5 to obtain a cathode slurry. The SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is activated carbon, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0057] S3. The LSCF-SDC electrode powder and organic glue are mixed evenly in a weight ratio of 2:1 to obtain an anode slurry. The LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0058] S4. SDC powder and pinene alcohol in a weight ratio of 1:1 are mixed evenly to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers with a thickness of 3 μm, and sintered at 1200°C for 5h to obtain an electrolyte with a structure of SDC|SSZ|SDC, where the SDC powder is Sm 0.2 Ce 0.8 O2 powder;
[0059] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form a SFM cathode layer with a thickness of 25 μm, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form a LSCF-SDC anode layer with a thickness of 25 μm, and sintering at 1300° C. for 5 h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0060] S6. A rare earth salt solution with a concentration of 0.5 mol / L and a surfactant in a weight ratio of 1:0.03 are uniformly mixed to obtain a rare earth solution, and the rare earth solution is impregnated with a microsyringe on the outer surface of the SFM cathode layer obtained in step S5 under a vacuum environment, and then dried at 80°C for 1.5h and sintered at 600°C for 1h, wherein the rare earth salt is Ce(NO3)3·6H2O and the surfactant is urea;
[0061] S7. Repeat step S6 to make the weight ratio of Ce(NO3)3·6H2O to SFM electrode powder 0.1:1, and finally sinter at 800°C for 3h to obtain a rare earth modified all-solid-state electrolytic cell;
[0062] S8. The all-solid-state electrolytic cell obtained in step S7 was sealed on an alumina tube, the temperature was raised to 800°C, CO2 and H2O with a volume ratio of 9:1 were introduced into the SFM cathode layer, and 2A·cm -2 The composition of the synthesis gas was tested by gas chromatograph (GC).
[0063] Example 4
[0064] The synthesis gas is prepared as follows:
[0065] S1. Pour SSZ powder into a mold and press it under 10MPa pressure to form a cylindrical SSZ blank with a bottom diameter of 20mm. Sinter the SSZ blank at 1400℃ for 10h to obtain a 150μm thick SSZ electrolyte layer. The SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 Powder;
[0066] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly in a weight ratio of 1:1:0.5 to obtain a cathode slurry. The SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is graphite, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0067] S3. The LSCF-SDC electrode powder and organic glue are mixed evenly at a weight ratio of 0.5:1 to obtain an anode slurry. The LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0068] S4. SDC powder and pinene alcohol in a weight ratio of 1:1 are mixed evenly to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers with a thickness of 2 μm, and sintered at a high temperature of 1150°C for 6 hours to obtain an electrolyte with a structure of SDC|SSZ|SDC, wherein the SDC powder is Sm 0.2 Ce 0.8 O2 powder;
[0069] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form a SFM cathode layer with a thickness of 15 μm, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form a LSCF-SDC anode layer with a thickness of 15 μm, and sintering at 1100° C. for 5 h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0070] S6. A rare earth salt solution with a concentration of 0.1 mol / L and a surfactant in a weight ratio of 1:0.05 are uniformly mixed to obtain a rare earth solution, and the rare earth solution is impregnated with a microsyringe on the outer surface of the SFM cathode layer obtained in step S5 under a vacuum environment, and then dried at 80°C for 2h and sintered at 400°C for 2h, wherein the rare earth salt is Pr(NO3)3·6H2O and the surfactant is ethylene glycol;
[0071] S7. Repeat step S6 to make the weight ratio of Pr(NO3)3·6H2O to SFM electrode powder be 0.06:1, and finally sinter at 400°C for 5h to obtain a rare earth-modified all-solid-state electrolytic cell;
[0072] S8. The all-solid-state electrolytic cell obtained in step S7 was sealed on an alumina tube, the temperature was raised to 850°C, CO2 and H2O with a volume ratio of 1:1 were introduced into the SFM cathode layer, and 0.2A·cm -2 The current was measured to obtain the IV curve of the battery, and the composition of the synthesis gas was tested by gas chromatography (GC).
[0073] Example 5
[0074] The synthesis gas is prepared as follows:
[0075] S1. Pour SSZ powder into a mold and press it under 10MPa pressure to form a cylindrical SSZ blank with a bottom diameter of 20mm. Sinter the SSZ blank at 1600℃ for 5h to obtain a SSZ electrolyte layer with a thickness of 220μm. The SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 Powder;
[0076] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly in a weight ratio of 1:1:0.5 to obtain a cathode slurry. The SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is corn starch, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0077] S3. The LSCF-SDC electrode powder and organic glue are mixed evenly in a weight ratio of 3:1 to obtain an anode slurry. The LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0078] S4. SDC powder and pinene alcohol in a weight ratio of 1:1 are mixed evenly to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers with a thickness of 5 μm, and sintered at 1250°C for 3h to obtain an electrolyte with a structure of SDC|SSZ|SDC, where the SDC powder is Sm 0.2 Ce 0.8 O2 powder;
[0079] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form a SFM cathode layer with a thickness of 35 μm, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form a LSCF-SDC anode layer with a thickness of 35 μm, and sintering at 1400° C. for 1 h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0080] S6. A rare earth salt solution with a concentration of 0.5 mol / L and a surfactant in a weight ratio of 1:0.02 are uniformly mixed to obtain a rare earth solution, and the rare earth solution is impregnated with a microsyringe on the outer surface of the SFM cathode layer obtained in step S5 under a vacuum environment, and then dried at 80°C for 1h and sintered at 800°C for 1h, wherein the rare earth salt is Nd(NO3)3·6H2O and the surfactant is ethanol;
[0081] S7. Repeat step S6 to make the weight ratio of Nd(NO3)3·6H2O to SFM electrode powder be 0.06:1, and finally sinter at 800°C for 0.5h to obtain a rare earth-modified all-solid-state electrolytic cell;
[0082] S8. The all-solid-state electrolytic cell obtained in step S7 was sealed on an alumina tube, the temperature was raised to 850°C, CO2 and H2O with a volume ratio of 1:1 were introduced into the SFM cathode layer, and 0.2A·cm -2 The current was measured to obtain the IV curve of the battery, and the composition of the synthesis gas was tested by gas chromatography (GC).
[0083] Example 6
[0084] The synthesis gas is prepared as follows:
[0085] S1. Pour SSZ powder into a mold and press it under 10MPa pressure to form a cylindrical SSZ blank with a bottom diameter of 20mm. Sinter the SSZ blank at 1450℃ for 9h to obtain a 160μm thick SSZ electrolyte layer. The SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 Powder;
[0086] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly in a weight ratio of 1:1:0.5 to obtain a cathode slurry. The SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is PMMA, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0087] S3. The LSCF-SDC electrode powder and organic glue are mixed evenly in a weight ratio of 1:1 to obtain an anode slurry. The LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0088] S4. SDC powder and pinene alcohol in a weight ratio of 1:1 are mixed evenly to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers with a thickness of 4 μm, and sintered at 1180°C for 4 hours to obtain an electrolyte with a structure of SDC|SSZ|SDC, where the SDC powder is Sm 0.2 Ce 0.8 O2 powder;
[0089] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form a SFM cathode layer with a thickness of 20 μm, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form a LSCF-SDC anode layer with a thickness of 20 μm, and sintering at 1200° C. for 4 h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0090] S6. A rare earth salt solution with a concentration of 0.2 mol / L and a surfactant in a weight ratio of 1:0.04 were uniformly mixed to obtain a rare earth solution, and the rare earth solution was impregnated with a microsyringe on the outer surface of the SFM cathode layer obtained in step S5 under a vacuum environment, and dried at 80°C for 2h and then sintered at 700°C for 1.5h, the rare earth salt was Sm(NO3)3·6H2O, and the surfactant was triethanolamine;
[0091] S7. Repeat step S6 to make the weight ratio of Sm(NO3)3·6H2O to SFM electrode powder be 0.06:1, and finally sinter at 700°C for 1h to obtain a rare earth-modified all-solid-state electrolytic cell;
[0092] S8. The all-solid-state electrolytic cell obtained in step S7 was sealed on an alumina tube, the temperature was raised to 850°C, CO2 and H2O with a volume ratio of 1:1 were introduced into the SFM cathode layer, and 0.2A·cm -2 The current was measured to obtain the IV curve of the battery, and the composition of the synthesis gas was tested by gas chromatography (GC).
[0093] Example 7
[0094] The synthesis gas is prepared as follows:
[0095] S1. Pour SSZ powder into a mold and press it under 10MPa pressure to form a cylindrical SSZ blank with a bottom diameter of 20mm. Sinter the SSZ blank at 1550℃ for 8h to obtain a SSZ electrolyte layer with a thickness of 210μm. The SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 Powder;
[0096] S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly in a weight ratio of 1:1:0.5 to obtain a cathode slurry. The SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder, the pore-forming agent is activated carbon, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0097] S3. The LSCF-SDC electrode powder and organic glue are mixed evenly in a weight ratio of 1.5:1 to obtain an anode slurry. The LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:24;
[0098] S4. SDC powder and pinene alcohol in a weight ratio of 1:1 are mixed evenly to obtain an isolation layer slurry, and the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers with a thickness of 3 μm, and sintered at 1210°C for 5h to obtain an electrolyte with a structure of SDC|SSZ|SDC, where the SDC powder is Sm 0.2 Ce 0.8 O2 powder;
[0099] S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form a SFM cathode layer with a thickness of 25 μm, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form a LSCF-SDC anode layer with a thickness of 25 μm, and sintering at 1350° C. for 3 h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC;
[0100] S6. A rare earth salt solution with a concentration of 0.4 mol / L and a surfactant in a weight ratio of 1:0.03 are uniformly mixed to obtain a rare earth solution, and the rare earth solution is impregnated with a microsyringe on the outer surface of the SFM cathode layer obtained in step S5 under a vacuum environment, and then dried at 80°C for 1.5h and sintered at 600°C for 2h, wherein the rare earth salt is La(NO3)3·6H2O and the surfactant is citric acid;
[0101] S7. Repeat step S6 to make the weight ratio of La(NO3)3·6H2O to SFM electrode powder be 0.06:1, and finally sinter at 600°C for 2h to obtain a rare earth-modified all-solid-state electrolytic cell;
[0102] S8. The all-solid-state electrolytic cell obtained in step S7 was sealed on an alumina tube, the temperature was raised to 850°C, CO2 and H2O with a volume ratio of 1:1 were introduced into the SFM cathode layer, and 0.2A·cm -2 The current was measured to obtain the IV curve of the battery, and the composition of the synthesis gas was tested by gas chromatography (GC).
[0103] Comparative Example
[0104] The difference from Example 1 is that steps S6 and S7 are not included, and the electrolytic cell prepared is not modified with rare earth.
[0105] Experimental example
[0106] The polarization resistance and synthesis gas yield of the electrolytic cells prepared in Examples 1-7 and the comparative example were respectively measured according to GB / T 34582-2017. The test results are shown in Table 1.
[0107]
[0108] Table 1
[0109] As can be seen from Table 1, the polarization resistance and syngas yield of Examples 1-7 of the present invention are better than those of the comparative example. Some preparation steps of the comparative example are different from those of Example 1. Compared with Example 1, the polarization resistance of the comparative example is significantly increased and the syngas yield is significantly reduced, indicating that the rare earth modification used in the present invention can effectively reduce the polarization resistance of the all-solid-state electrolytic cell and increase the syngas yield of the all-solid-state electrolytic cell.
[0110] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing synthesis gas using a rare earth modified all-solid-state electrolytic cell, characterized in that: The following steps are involved: S1. The SSZ powder is poured into a mold and pressed into a cylindrical SSZ green billet, and the SSZ green billet is sintered at high temperature for 5-10h to obtain a SSZ electrolyte layer; S2. The SFM electrode powder, pore-forming agent and organic glue are mixed evenly to obtain a cathode slurry; S3. The LSCF-SDC electrode powder and the organic glue are mixed evenly to obtain an anode slurry; S4. The SDC powder and pinene alcohol are mixed evenly to obtain an isolation layer slurry, the isolation layer slurry is screen-printed on the upper and lower surfaces of the SSZ electrolyte layer obtained in step S1 to form two isolation layers, and the electrolyte is sintered at high temperature for 3-6h to obtain an SDC|SSZ|SDC electrolyte; S5. Screen-printing the cathode slurry obtained in step S2 on the outer surface of one of the isolation layers obtained in step S4 to form an SFM cathode layer, screen-printing the anode slurry obtained in step S3 on the outer surface of another isolation layer obtained in step S4 to form an LSCF-SDC anode layer, and sintering at high temperature for 1-5h to obtain a half-cell with a structure of SFM|SDC|SSZ|SDC|LSCF-SDC; S6. The rare earth salt solution and the surfactant are mixed to obtain a rare earth solution, and the rare earth solution is impregnated into the outer surface of the SFM cathode layer obtained in step S5 with a microsyringe under a vacuum environment, and then dried and sintered for 1-2h; S7. Repeat step S6, and finally sinter for 0.5-5h to obtain a rare earth-modified all-solid-state electrolytic cell; S8. The all-solid-state electrolytic cell obtained in step S7 is sealed on an alumina tube, CO2 and H2O are introduced into the SFM cathode layer after heating, and then current is applied to achieve the preparation of synthesis gas.
2. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In step S1, the SSZ powder is (Sc2O3) 0.1 (CeO2) 0.01 (ZrO2) 0.89 Powder, the pressing pressure is 10MPa, and the bottom diameter of the SSZ green billet is 20mm; The high temperature sintering temperature is 1400-1600°C, and the thickness of the electrolyte layer is 150-220 μm.
3. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In the step S2, the weight ratio of SFM electrode powder, pore-forming agent and organic glue is 1:1:0.5, and the SFM electrode powder is Sr2Fe 1.5 Mo 0.5 O 6-δ The powder is a pore-forming agent selected from one or more of activated carbon, graphite, corn starch or PMMA, and the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:
24.
4. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In the step S3, the weight ratio of LSCF-SDC electrode powder to organic glue is (0.5-3):1, and the LSCF-SDC electrode powder is La 0.6 Sr 0.4 Co 0.2 Fe 0.8 -Sm 0.2 Ce 0.8 O2 powder, the organic glue is composed of ethyl cellulose and pinene alcohol in a weight ratio of 1:
24.
5. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In step S4, the weight ratio of SDC powder to terpineol is 1:1, and the SDC powder is Sm 0.2 Ce 0.8 O2 powder; the high temperature sintering temperature is 1150-1250°C, and the thickness of the isolation layer is 2-5μm.
6. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In the step S5, the high temperature sintering temperature is 1100-1400° C., and the thickness of the SFM cathode layer and the LSCF-SDC anode layer are both 15-35 μm.
7. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In the step S6, the weight ratio of the rare earth salt solution and the surfactant is 1:(0.02-0.05), the concentration of the rare earth salt solution is 0.1-0.5 mol / L, the rare earth salt is one or more of the nitrates or chlorides of the elements Ce, Pr, Sm, Gd, Nd, and La, and the surfactant is one or more of citric acid, glycine, urea, ethylene glycol, ethanol, or triethanolamine; the drying temperature is 80°C, the drying time is 1-2h, and the sintering temperature is 400-800°C.
8. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In the step S7, the weight ratio of the rare earth salt to the SFM electrode powder is (0.02-0.1):1, and the sintering temperature is 400-800°C.
9. The method for preparing synthesis gas by a rare earth modified all-solid-state electrolytic cell according to claim 1, characterized in that: In step S8, the temperature of the heating is 650-850°C, the volume ratio of the introduced CO2 and H2O is (0.1-9):1, and the current density is 0.1-2A·cm -2 .
Citation Information
Cited By
All-solid-state electrolytic cell electrolytic catalytic material as well as preparation method and application thereof
CN121874853A
All-solid-state electrolytic cell electrolysis catalyst materials, preparation methods and applications
CN121874853B